The Role of the Land Deed Officials in the Implementation of Electronic Land Certification in Indonesia - Wanda Desvira Putri, Adelia; Sunardi, Sunardi; Siboy, Ahmad (Law Development Journal, 2026)
Land registration is a series of continuous governmental activities, encompassing the collection and maintenance of physical and juridical data, as well as the issuance of proof of land rights and the recording of other rights attached thereto. The purpose of land registration is to provide legal certainty and protection through the issuance of certificates as valid evidence. The Land Deed Official (PPAT) is authorized to draw up land deeds as the basis for the issuance of certificates, thus playing an essential role in ensuring the validity and security of transactions. In order to modernize public services and support national progress in the land sector, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) has implemented a policy on the issuance of electronic land certificates.Based on this background, the formulation of the problems in this research is as follows: first, how is the role of the Land Deed Official (PPAT) in maintaining the validity of land certificate data within the electronic land service system; and second, what are the authority and responsibilities of the Land Deed Official (PPAT) in the process of electronic land rights services in accordance with the applicable regulations. This research employs a normative legal research method using statutory, conceptual, and historical approaches. The legal materials consist of primary legal materials in the form of laws and regulations related to land certificate registration and Land Deed Officials, secondary legal materials in the form of legal literature and previous research, and tertiary legal materials as supporting sources. The analysis is conducted qualitatively through interpretation and legal construction of statutory regulations and relevant doctrines. The results of this study affirm that the Land Deed Official (PPAT) possesses juridical authority to draw up authentic deeds related to the registration of electronic land certificates. The Land Deed Official (PPAT) ensures the security and transparency of the process, thereby reducing land disputes. The Land Deed Official (PPAT) is responsible for ensuring the validity of data through the integrated system of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) by requiring the submission of electronic documents.